Physical, Psychological, and Cognitive Profile of Post-COVID Conditions in Healthcare Workers, Quebec, Canada. (1st August 2022) - Carazo, Sara; Skowronski, Danuta M; Laforce, Robert; Talbot, Denis; Falcone, Emilia L; Laliberté, Denis; Denis, Geoffroy; Deshaies, Pierre; Hegg-Deloye, Sandrine; De Serres, Gaston
Abstract: Background: The prevalence of post-COVID conditions (PCC) and associated physical, psychological, and cognitive symptoms was assessed among Quebec healthcare workers (HCWs) with coronavirus disease 2019 (COVID-19). Methods: This case-control study compared 6061 symptomatic HCWs with polymerase chain reaction–confirmed COVID-19 between July 2020 and May 2021 with a random sample of 4390 symptomatic HCWs who were test-negative controls. The prevalence of physical symptoms lasting ≥4 weeks (PCC4w) or ≥12 weeks (PCC12w) was estimated among hospitalized and nonhospitalized cases. In multivariate models, sociodemographic and clinical characteristics, as well as vaccine history, were evaluated as potential risk factors. Prevalence ratios compared 4 aspects of self-reported cognitive dysfunction among PCC cases to controls, adjusting for psychological distress and fatigue. Results: PCC4w and PCC12w prevalences of 46% (2746/5943) and 40% (653/1746), respectively, were observed among nonhospitalized cases and 76% (90/118) and 68% (27/37), respectively, among hospitalized cases. Hospitalization, female sex, and age were associated with higher PCC risk. A substantial proportion of nonhospitalized PCC4w cases often or very often reported cognitive dysfunction, including concentration (33%) or organizing (23%) difficulties, forgetfulness (20%), and loss of necessary items (10%). All 4 aspects of cognitive dysfunction were associated with PCC4w symptoms, psychological distress, and fatigue. Conclusions: PCC may be a frequent sequela of ambulatory COVID-19 in working-age adults, with important effects on cognition. With so many HCWs infected, the implications for quality healthcare delivery could be profound if cognitive dysfunction and other severe PCC symptoms persist in a professionally disabling way. Further evaluation of PCC prevalence and prognosis is warranted. Abstract : Among 6061 healthcare workers in Quebec, prevalence of ≥12-week post-COVID conditions was 40% and 68% among nonhospitalized and hospitalized cases, respectively. Over 30% of nonhospitalized cases reported cognitive dysfunction, which was associated with persistent physical symptoms, psychological distress, and fatigue.